Mapping QTLs for seedling characteristics under different water supply conditions in rice (Oryza sativa) - Cui, Kehui; Huang, Jianliang; Xing, Yongzhong; Yu, Sibin; Xu, Caiguo; Peng, Shaobing (Wiley, 2008)
A greater understanding of the genetics of responses to water deficit/drought may be helpful in improving water‐deficit resistance in the early stages of growth in rice. A recombinant inbred population derived from a cross between Zhenshan 97 and Minghui 63 was grown in hydroponic culture to characterize the responses of seedlings to water deficit imposed by PEG 6000 and to identify quantitative trait loci (QTLs) for seedling characteristics under both well‐watered and water‐deficit conditions. Generally, the two parents showed significant differences in plant height (PH), maximum root length (MRL), shoot fresh weight (SFW), root fresh weight (RFW), number of roots and root:shoot ratio based on fresh weight under both well‐watered and water‐deficit conditions. For two parents, PH and SFW were significantly inhibited under water deficit. However, the other four traits had larger values under water deficit. Among 26 and 34 QTLs detected for the six traits studied under the well‐watered and water‐deficit conditions, respectively, a total of 14 QTLs for SFW, PH, RFW and MRL (23% of total QTLs detected) were detected in similar or tight linkage regions in both conditions. Among 11 intervals on 7 chromosomes identified to harbor multiple QTLs, 8 intervals were found to affect related traits under the two water supply conditions and 3 intervals were observed to be water supply‐specific regions and had effects only under well‐watered conditions, suggesting that water supply‐specific regions or QTLs may be closely associated with the responses of lines to water deficit in the study. Several regions for the traits studied were also found to affect the root‐related traits in previous studies and might be used in marker‐assisted selection for drought‐resistant rice in breeding programs.